PENENTU PERILAKU BERINVESTASI - Widayat, Widayat (Journal of Innovation in Business and Economics, 2010)
Modern Financial theory  based on  assumption that individual   investment decision is  rationaly. Occurance anomalies   indicate   that investment choice  is not always rational. Irrationality in the field of investment  tend to   develop the theory of behavior investment. The  theory   of finance behavior  catalyzed by sociology, psychology and also finance. According to this theory, economics decision and investment decision   as a integrated behavior, affected by many antecendence variables. Financial literacy, socio demography aspect, attitude toward risk  are influence  investment behavior. Besides external factor for example economics condition also affecting behavior of investment.